Tropical Volcanic Soils From Flores Island, Indonesia - Hikmatullah Hikmatullah; Kesumo Nugroho (UNIVERSITY OF LAMPUNG, 2010)
Tropical Volcanic Soils from Flores Island, Indonesia (Hikmatullah and K Nugroho): Soils that are developed in tropical region with volcanic parent materials have many unique properties, and high potential for agricultural use. The purpose of this study is to characterize the soils developed on volcanic materials from Flores Island, Indonesia, and to examine if the soils meet the requirements for andic soil properties. Selected five soils profiles developed from andesitic volcanic materials from Flores Island were studied to determine their properties. They were compared in their physical, chemical and mineralogical characteristics according to their parent material, and climatic characteristic different. The soils were developed under humid tropical climate with ustic to udic soil moisture regimes with different annual rainfall. The soils developed from volcanic ash parent materials in Flores Island showed different properties compared to the soils derived from volcanic tuff, even though they were developed from th e same intermediary volcanic materials. The silica contents, clay mineralogy and sand fractions, were shown as the differences. The different in climatic conditions developed similar properties such as deep solum, dark color, medium texture, and very friable soil consistency. The soils have high organic materials, slightly acid to acid, low to medium cation exchange capacity (CEC). The soils in western region have higher clay content and showing more developed than of the eastern region. All the profiles meet the requirements for andic soil properties, and classified as Andisols order. The composition of sand mineral was dominated by hornblende, augite, and hypersthenes with high weatherable mineral reserves, while the clay fraction was dominated by disordered kaolinite, and hydrated halloysite. The soils were classified into subgroup as Thaptic Hapludands, Typic Hapludands, and Dystric Haplustands.